THE IMPACTS OF THE COVID-19 PANDEMIC ON ELECTIVE SURGERIES - Martins Rodrigues, Veridiana; Eduarda Almeida de Souza , Cicera; Lívia Silva Fonseca Moreira de Medeiros, Renata; Caroline de Souza, Anne; Silva Oliveira, Geane (Health and Society, 2023)
Introduction: The pandemic caused damage globally, the realities of entire societies were affected and had to adapt to different scenarios and sensitivities. Among the damage caused, it can be noted that in the private sector scenario, the number of elective surgeries gradually decreases. The situation experienced by the public during the peak of the pandemic caused interruptions in elective surgeries, as the spread of the virus affected the hospital routine and led to the suspension of non-urgent procedures. Objective: To highlight the impacts of Covid-19 on scheduling and performing elective surgeries. Methodology: this is an integrative literature review, whose purpose is to investigate evident answers to the topic in question, where a survey of data was carried out in the scientific bases: LILACS, SCIELO and MEDLINE. Results and Discussion: The results indicate that, in the face of the pandemic, many health systems chose to postpone or cancel non-emergency elective surgeries, allocating resources for the treatment of patients with COVID-19 and aiming to reduce the exposure of patients and health professionals to the virus. This culminated in a considerable decrease in the performance of elective surgeries in various specialties, such as orthopedics, plastic surgery, ophthalmology, among others. Conclusion: Additionally, the investigation revealed that the pandemic also had impacts on the ability of hospitals to provide adequate perioperative care. In short, the search for a balance between the continuity of health services and safeguarding against the virus is a constant process, in which lessons learned from the past will influence choices and initiatives in the future.